2006
DOI: 10.1103/physrevd.73.052005
|View full text |Cite
|
Sign up to set email alerts
|

Improved measurement of thebb¯production cross section in 920 GeV fixed-target proton-nucleus collisions

Abstract: A new measurement of the b b production cross section in 920 GeV proton-nucleus collisions is presented by the HERA-B Collaboration. The b b production is tagged via inclusive bottom quark decays into J= mesons by exploiting the longitudinal separation of J= ! l l ÿ decay vertices from the primary proton-nucleus interaction point. Both e e ÿ and ÿ channels are reconstructed for a total of 83 12 inclusive b ! J= X events found. The combined analysis yields a b b to prompt J= cross section ratio of b b J= 0:032 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…These measurements can be compared to the global trend of the bb cross section as a function of ffiffi ffi s p [27][28][29]31,[67][68][69][70][71][72], as shown in Fig. 29.…”
Section: Bottom Cross Sectionmentioning
confidence: 99%
“…These measurements can be compared to the global trend of the bb cross section as a function of ffiffi ffi s p [27][28][29]31,[67][68][69][70][71][72], as shown in Fig. 29.…”
Section: Bottom Cross Sectionmentioning
confidence: 99%
“…BR photons emitted before the magnet are searched for in the ECAL and the momentum of the electron is corrected if such a cluster is found. Details of this procedure are explained in [18].…”
Section: Event Selectionmentioning
confidence: 99%
“…Cross section measurements for bottom production in hadron-hadron collision experiments have been made from lower energy fixed-target experiments [2][3][4] ( √ s < 45 GeV) up to collider energies ( √ s > 100 GeV). It was found that pQCD predictions match experimental results well at energies greater than √ s = 1 TeV [5][6][7][8][9][10][11][12], but less so at lower energies.…”
Section: Introductionmentioning
confidence: 99%